ANALISIS FAKTOR INDIVIDU DAN FAKTOR LINGKUNGAN FISIK TERHADAP STRES KERJA PADA PEKERJA PROYEK REVITALISASI TRANSJAKARTA PT WIJAYA KARYA TAHUN 2022 - Andia Nabila (2023)
Occupational stress is a physical and mental response that occurs due to changes and pressures at work which can trigger various health problems plus decreased performance and productivity. The purpose of this study was to analyze the relationship between individual factors (age, marital status, education and duration of employment) and physical environment factors (hot work climate and noise) with occupational stress amid the workers of PT Wijaya Karya's Transjakarta Revitalization Project. This quantitative study was conducted using a cross-sectional design with a total of 100 workers using the total sampling technique. The results of the Rank Spearman correlation test showed age (p-value = 0.000, (r) = 0.791), duration of employment (p-value = 0.000, (r) = 0.825), hot work climate (p-value = 0.000, (r) = 0.428) and noise (p-value = 0.000, (r) = 0.461) have a significant relationship with occupational stress. The results of the Mann-Whitney mean difference test on marital status (p-value = 0.000) and education (p-value = 0.000) also showed a significant relationship with occupational stress. It can be concluded that individual and physical environment factors are related to occupational stress, the existing Occupational Health and Safety Management System must be improved by installing engine dampers, providing drinking water and shelter, implementing a work rotation system and using the right PPE. Keywords: Individual factors, noise, climate, occupational stress